2019
DOI: 10.35891/ml.v11i1.1726
|View full text |Cite
|
Sign up to set email alerts
|

Haji Backpacker : Peluang Dan Tantangan

Abstract: Backpacking activity at religious sites represents an important spiritual journey . However, not all religious sites are locations able to accommodate large numbers of visitors at one time, or are able to resolve some of the conflicts that arise from governance. From accomodation, hajj regulation until punishment for those who entry Mekah without letter of permision.this paper is going to review of planning and management solutions used on hajj backpacker associated with regulation to tackle the pressures of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous studies on Muslim pilgrimage focused on Hajj and existing research on Umrah tended to concentrate on identifying several sets of practices for service quality and the criteria for selecting an Umrah travel agency (Bashir et al, 2017;Muhammad and Artanti, 2016;Muslim et al, 2020). The only studies on Umrah DIY were found to have focused on the feasibility of Umrah backpackers among young Indonesian travellers (Lailatul and Melinda, 2018;Fakhruddin and Ubaidillah, 2021), and Hajj backpackers regarding the possibilities and obstacles of religious travellers (Kusumaningtyas, 2019). Findings highlight budget conscious travellers and the need for flexibility as it has also been documented for other forms of independent travel such as backpacking.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on Muslim pilgrimage focused on Hajj and existing research on Umrah tended to concentrate on identifying several sets of practices for service quality and the criteria for selecting an Umrah travel agency (Bashir et al, 2017;Muhammad and Artanti, 2016;Muslim et al, 2020). The only studies on Umrah DIY were found to have focused on the feasibility of Umrah backpackers among young Indonesian travellers (Lailatul and Melinda, 2018;Fakhruddin and Ubaidillah, 2021), and Hajj backpackers regarding the possibilities and obstacles of religious travellers (Kusumaningtyas, 2019). Findings highlight budget conscious travellers and the need for flexibility as it has also been documented for other forms of independent travel such as backpacking.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Existing research on Muslim pilgrimages is focused more on Hajj (Kusumaningtyas, 2019;Almuhrzi and Alsawafi, 2017;Raj and Bozonelos, 2015) rather than on the Umrah. Hajj is only performed once a year in the month of Dhul-Hijjah, and pilgrims must wait for a quota vacancy.…”
Section: Introductionmentioning
confidence: 99%